Potret Implementasi Teori Dick and Carey dalam Pembuatan Modul Ajar PAI Di SMPN 1 Siman - Yoga Nuryuliawan (Muaddib: Jurnal Pendidikan Agama Islam, 2025)
This research examines the application of Dick and Carey's theory in developing Islamic Religious Education (PAI) teaching modules at SMPN 1 Siman. This theory is applied to design modules that are structured, interactive, and appropriate to student needs. The process of applying this theory involves several important stages, namely identifying learning objectives, analyzing student needs, designing learning strategies, as well as formative and summative evaluation. First, the learning objectives are set to increase students' understanding of Al-Qur'an and Hadith material, as well as form spiritual character and discipline. Next, an analysis of students' needs is carried out to understand their background, potential and learning styles. Based on the results of this analysis, interactive learning strategies and using learning technology are designed to facilitate students in understanding the material more interestingly and effectively. During the learning process, diagnostic evaluations are carried out to determine students' initial understanding, as well as formative evaluations to provide useful feedback. Summative evaluation is carried out at the end of learning to measure goal achievement. This approach is adapted to the Merdeka Curriculum, which emphasizes flexibility and student character development. The research results show that the application of this theory is successful in improving the quality of learning and meeting students' needs effectively.